2019
DOI: 10.2478/emj-2019-0015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Modern Process Performance Indicators on Corporate Performance — the Empirical Study

Abstract: A B S T R A C TThe increasing pressure of globalisation on the worldwide market has forced enterprises to shift their focus from product quality to effectiveness of internal business processes. The object of interest of this paper is a modern management approach based on corporate performance evaluation by measuring the performance of internal processes. The paper aims to prove that the use of modern indicators and the measurement of internal processes belong among factors that have a direct positive impact on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Six Sigma is a popular quality improvement methodology that aims to significantly improve the quality of a manufacturing process and reduce costs by minimising process variation and reducing defects (Breyfogle and Meadows, 2001;Breyfogle et al, 2001, Sujová et al, 2019. In a manufacturing or assembly process, all its sub-processes are known to inherently possess a variation (Juran and Godfrey, 1999;Mckay and Steiner, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Six Sigma is a popular quality improvement methodology that aims to significantly improve the quality of a manufacturing process and reduce costs by minimising process variation and reducing defects (Breyfogle and Meadows, 2001;Breyfogle et al, 2001, Sujová et al, 2019. In a manufacturing or assembly process, all its sub-processes are known to inherently possess a variation (Juran and Godfrey, 1999;Mckay and Steiner, 1997).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This was supported by the work of Esokomi and Otuya (2020) in the study of the impact of financial re-engineering on the financial performance of Kenyan cooperative societies as a service organisation. Sujová, Marcineková, and Simanová (2019) introduced the increasing pressure of globalisation impacting on corporate performance and resulting into a more positive Return on Equity (ROE). The study went further to recommend using modern process indicators for better financial performance.…”
Section: Empirical Review -Financial Re-engineering and Financial Per...mentioning
confidence: 99%
“…Research results confirmed a positive influence of changes in business processes on corporate performance (Remeň & Sujová, 2018). To reach higher performance is possible by using modern process methods and indicators (Sujová et al, 2019).…”
Section: Introductionmentioning
confidence: 99%